Introducing a professional development framework for postgraduate medical supervisors in secondary care: considerations, constraints and challenges. Issue 1014 (30th March 2010) - Swanwick, Tim; McKimm, Judy; Clarke, Robert
Abstract : Purpose of study: As the duration of postgraduate training becomes shorter, direct patient contact time is reduced, and supervision becomes more distributed, there is a move to 'professionalise' postgraduate medical education. This paper reports an initiative in one postgraduate training institution (the London Deanery) to develop and introduce a developmental framework and system of portfolio-based review of educational supervisors in the secondary care setting. Study design: 16 acute, mental health, foundation and primary-care Trusts participated in a pilot project, which was subsequently evaluated using focus groups and a semistructured questionnaire. Results: Thematic analysis of transcripts identified a number of considerations, constraints and challenges, important observations given the current policy intention of the UK health departments to introduce mandatory training and performance review for educational supervisors. Conclusion: This pilot study shows that such a process can be implemented at local level if facilitated by a clear and unambiguous developmental framework that can be applied flexibly across all specialities. Systems of review also need to be simple and straightforward, take into account existing appraisal processes, and simultaneously address issues of motivation, recognition and reward.